ملامح الرؤية الكونية عند الشيخ محمد الغزالي - لمقدم, سهيلة; نجعي, وحيدة (University of Eloued جامعة الجزائر, 2020)
"تناولنا في دراستنا العقدية لرسالة الماستر الموسومة بعنوان: ملامح الرؤية الكونية الإسلامية عند الشيخ محمد الغزالي (ت1997م) وهو شخصية مهمة في العالم الإسلامي، حيث تطرق فيها لنظرته الكونية من خلال أبرز مؤلفاته التي عالجت هذا الموضوع بشكل مباشر وهي: عقيدة المسلم، والمحاور الخمسة للقرآن الكريم، ونظرات في القرآن، والجانب العاطفي في الإسلام، فما هي ملامح الرؤية الكونية الإسلامية في فكر الشيخ محمد الغزالي؟ فقد درس من خلال كتبه العناصر الثلاثة لرؤيته الكونية وهي كالتالي: (الله والإنسان والكون). أولاً فيما يخص رؤيته الكونية في الله تعالى: فقد عمل مبرهناً ومثبتاً على وجود الله تعالى وراداً على الملحدين فيما زعموه بنفي وجوده، وإثبات وحدانيته ونفي الشريك عنه وتنزيهه عن كل صفات النقص وإثبات كل صفات كمال له فهو فرد أحد صمد. ثانياً فيما يخص رؤيته الكونية في الإنسان: في علاقته مع الله بتوحيده وتخليصه من المفاهيم الشركية الزائغة والعقائد الزائفة من الديانات المحرفة والباطلة والرد عن الفلسفات بما فيها المادية والجدلية ممتثلاً إلى أوامره واجتناب نواهيه، فقد سخر له المخلوقات من أجل خدمته وتسخيره له باعتباره كائن مفضل ومخدوم مكرم خلقه بيده الشريفة وكرمه على سائر خلقه، وأن نفخ فيه من روحه من أجل الوظيفة التي خلق من أجلها ألا وهي عبادته لله تعالى، وفي علاقته مع أخيه الإنسان كبر الوالدين وتربية الأبناء، وتطرق لأصل خلقه وحسن تقويمه من تراب، ثم تحدث عن مصيره وأجاب عن الأسئلة الوجودية من أين وجد؟ وإلى أين مآله؟ ولماذا وجد؟ وعن مصير الكون كيف وجد؟ ولماذا؟، وفي علاقته مع نفسه في ثنائية الروح والجسد، ليؤدي وظيفته الإستخلافية ويعيد مجد حضارة الإسلام. ثالثاً ثم تحدث عن الكون: أن الله سبحانه خلقه وخلق ما فيه من حيوان ونبات وجماد فالرؤية الكونية تجيب من وجهة نظر الإمام عن مصير الكون كيف وجد؟ ولماذا؟ وما هي نهايته؟ كما وضحته الآيات القرآنية الكريمة التي استقاها الغزالي من المصادر الإسلامية كالقرآن الكريم والأحاديث النبوية الشريفة. " Research Summary: In our doctrinal study of the Master’s Thesis tagged with the title: Features of the Islamic Cosmic View of Sheikh Muhammad al-Ghazali (d.1997 CE), he is an important figure in the Islamic world, in which he touched upon his cosmic view through his most prominent books that dealt with this topic directly, namely: The Muslim’s Creed and The Five Axes of the Qur’an The Noble Qur'an, looks at the Qur’an, and the emotional aspect of Islam. What are the features of the Islamic cosmic vision in the thought of Sheikh Muhammad al-Ghazali? He studied through his books the three elements of his cosmic vision, which are as follows: (God, man and the universe). First, with regard to his cosmic vision in God Almighty: He worked as proof and proof of the existence of God Almighty and as a guide to atheists in what they claimed to deny his existence, prove his oneness, banish the partner from him, and clear him from all the qualities of deficiency and prove all the qualities of perfection for him, for he is an individual who has steadfast Secondly, with regard to his universal vision in man: In his relationship with God by unifying him and ridding him of erratic polytheistic concepts and false doctrines from distorted and invalid religions, rejecting philosophies, including materialism and dialectic, in compliance with his orders and avoiding his prohibitions. His creation is honored with his honorable hand and generosity over the rest of his creation, and he breathed into him from his soul for the sake of the position for which he was created, namely his worship of God Almighty, and in his relationship with his fellow man, the parents and the upbringing of children grew up, touched on the origin of his creation and his righteousness from dust, then he spoke about his fate and answered For existential questions, where is he found? And where is its destination? And why was he found? And about the fate of the universe, how was it found? And why ?, and in his relationship with himself in the duality of soul and body, to perform his heuristic function and restore the glory of the Islamic civilization. Thirdly, then he talked about the universe: that God Almighty created him and created what is in it of animals, plants and inanimate objects. The cosmic vision answers from the Imam’s point of view about the fate of the universe, how was it found? Why? What is its end? It was also illustrated by the noble Qur’an verses that Al-Ghazali gleaned from Islamic sources such as the Holy Qur’an and the noble Prophet’s hadiths.
مذكرة ماستر تخصص عقيدة
Keywords: الرؤية الكونية الإسلامية، الإمام الغزالي، (الله، الإنسان، الكون).; the Islamic cosmic vision, Imam Al-Ghazali, (God, man, the universe).